RF Receiver front end for 28.5 GHz applications on a 70 GHz F-T SiGe BiCMOS process - Fortes, Fernando (2012)
This article presents the design and test of a receiver front end aimed at LMDS applications at 28.5 GHz. It presents a system-level design after which the receiver was designed. The receiver comprises an LNA, quadrature mixer and quadrature local oscillator. Experimental results at 24 GHz center frequency show a conversion voltage gain of 15 dB and conversion noise figure of 14 5 dB. The receiver operates from a 2 5 V power supply with a total current consumption of 31 mA.